Romanticism and Time : Literary Temporalities. - Laniel-Musitelli, Sophie. (Open Book Publishers, 2021)
'Eternity is in love with the productions of time'. This original edited volume takes William Blake's aphorism as a basis to explore how British Romantic literature creates its own sense of time. It considers Romantic poetry as embedded in and reflecting on the march of time, regarding it not merely as a reaction to the course of events between the late-eighteenth and mid-nineteenth centuries, but also as a form of creative engagement with history in the making.